2022
DOI: 10.3390/w14213391
|View full text |Cite
|
Sign up to set email alerts
|

Combined Transcriptome and Metabolome Analysis of a New Species of Microalgae from the Tibetan Plateau and Its Response to Sewage Treatment

Abstract: Microalgae are pivotal in maintaining water quality in the lakes and rivers of Qinghai-Tibet plateau. The optimum sewage treatment conditions for Desmodesmus sp. Are, temperature: 20–25 °C, light intensity: 3000–8000 lx, and pH: 7.0–7.5, identified based on orthogonal experiments. The maximum removal rate of total nitrogen, total phosphorus, and chemical oxygen demand was more than 95% in the actual sewage treatment. The sewage treatment capacity of Desmodesmus sp. From plateau is higher than that from plains … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(1 citation statement)
references
References 41 publications
0
1
0
Order By: Relevance
“…is widely used in sewage treatment. Wang et al (2022) concluded that the maximum removal rate of total nitrogen, total phosphorus, and chemical oxygen demand by Desmodesmus sp. in actual wastewater treatment exceeded 95%.…”
Section: Introductionmentioning
confidence: 99%
“…is widely used in sewage treatment. Wang et al (2022) concluded that the maximum removal rate of total nitrogen, total phosphorus, and chemical oxygen demand by Desmodesmus sp. in actual wastewater treatment exceeded 95%.…”
Section: Introductionmentioning
confidence: 99%